The Heat Treatment effect of Nickel-coated Steel Plate Substrate by Electroless Plating on Hardness Test - Hirary, Marisa; Ramelan, Aditianto; ., . (International Journal of Engineering and Technology, 2018)
The present study was aimed to analyze the effect of heat treatment on phase change of thin layer of nickel on steel plate substrate. The coating process was electroless plated using chemical solution. This work requires nickel solution as the main component of coating. Substrate was coated by electroless nickel plating at pH 7.5 and temperature was 85 â„ƒ for 100 minutes with heat treatment for 30 minutes at temperature are 320 â„ƒ and 340 â„ƒ. Furthermore, the substrate will be analyzed with metallography method to obtain visualization of thickness on plate surface. The result show that the layer on steel surface has a uniform thickness. Based on the hardness test, the heated plated resulting the better performance compared with the non-heated one. Surface hardness increased from 134VHN to 646VHN with a coating thickness of 17.49Î¼m and a XRD characterization showed a broadened Ni peak. After heat treatment at temperature are 320â„ƒ and 340â„ƒ, the surface hardness increased up to 851VHN and 1020VHN.Â Â